Review of Three Latent Class Cluster Analysis Packages: Latent Gold, poLCA, and MCLUST. - Haughton, Dominique; Legrand, Pascal; Woolford, Sam (American Statistician, 2009)
A review of three software packages that can be used to perform latent class cluster analysis—Latent Gold®, MCLUST, and poLCA—is presented. A single dataset is used, and each software package is applied to develop a latent class cluster analysis for the data, which allows for the comparison of the features and the resulting clusters from each software package. The strengths and weaknesses of each software package are discussed and compared in terms of usability, cost, data characteristics, and performance. Factors to consider when choosing a package are suggested.